The Gini Coefficient and Personal Inequality Measurement - James Davies (Center for Economic Studies and ifo Institute (CESifo), 2016)
The Gini coefficient is based on the sum of pairwise income differences, which can be decomposed into separate sums for individuals. Differences with poorer people represent an individual's advantage, while those with richer people constitute deprivation. Weighting deprivation and advantage differently produces a family of “Gini admissible” personal inequality indexes, whose population average equals the Gini. Properties of the personal indexes illuminate those of the Gini. Secular changes in income distribution are analyzed. During economic development traditional sector people may view inequality as constantly increasing while others believe the opposite. Personal views about polarization and rising inequality are also discussed.
Keywords: D30; D63; 330